The Effect of Environmental Performance and Agency Cost on Financial Performance - Augustin, Lestari; Anjelia, Viona; Hirmaleny, Yenny; Suripto, Suripto (Institut Bisnis dan Informatika Kesatuan, 2024)
This study examines the impact of environmental performance and agency cost on financial performance. The population of this study consists of manufacturing companies listed on the Indonesian Stock Exchange (BEI) from 2018 to 2022. A total of 162 observations from 27 companies were obtained using purposive sampling. The study employs a quantitative approach and uses panel data regression analysis with E-Views 10 software. The results show that environmental performance and agency cost have a simultaneous impact on financial performance. However, environmental performance does not have a significant impact on financial performance, while agency cost does. The study recommends that companies pay attention to agency cost to maintain their financial performance.